2008
DOI: 10.1177/0894845308316293
|View full text |Cite
|
Sign up to set email alerts
|

School Engagement Among Urban Youth of Color

Abstract: School engagement is a multifaceted psychosocial process that functions as a key mediator of academic achievement, motivation, and school dropout. This study investigated the effects of vocational exploration and racial identity on behavioral (attendance, attention, time spent on class work) and psychological (identification with school) factors of school engagement among urban youth of color (N = 197). Hierarchical multiple regression and criterion-pattern analysis revealed a predictive profile marked by high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(14 citation statements)
references
References 75 publications
1
13
0
Order By: Relevance
“…Studies using measures of emotional and psychosocial engagement have found positive relationships to academic test performance (Borman & Overman, 2004), student grade point averages (Gonzalez & Padilla, 1997), and better student attendance at school (Finn & Rock, 1997;Klem & Connell, 2004). Further, school engagement research has indicated that students who regard their education as relevant and purposive in preparing them to achieve future goals are much more likely to perform well in school and stay in school to graduate (Perry, 2008). Enhanced school engagement not only reduces risks of poor outcomes, such as living in poverty, receiving public assistance, and having poor health outcomes (Blafanz et al, 2009), but also increases the likelihood of students continuing to college or making a successful transition into a job or career (Fredricks et al, 2004).…”
Section: School Engagementmentioning
confidence: 93%
See 1 more Smart Citation
“…Studies using measures of emotional and psychosocial engagement have found positive relationships to academic test performance (Borman & Overman, 2004), student grade point averages (Gonzalez & Padilla, 1997), and better student attendance at school (Finn & Rock, 1997;Klem & Connell, 2004). Further, school engagement research has indicated that students who regard their education as relevant and purposive in preparing them to achieve future goals are much more likely to perform well in school and stay in school to graduate (Perry, 2008). Enhanced school engagement not only reduces risks of poor outcomes, such as living in poverty, receiving public assistance, and having poor health outcomes (Blafanz et al, 2009), but also increases the likelihood of students continuing to college or making a successful transition into a job or career (Fredricks et al, 2004).…”
Section: School Engagementmentioning
confidence: 93%
“…In particular, recent research has found that middle school performance and school engagement were critical interim school outcomes and important predictors of high school graduation (Blafanz, Fox, Bridgeland, & McNaught, 2009). Students who consider their education as relevant and preparing them to achieve future goals are also more likely to perform well in school and graduate (Perry, 2008). Student engagement has been shown to be responsive to the social and learning environment of the classroom and the school (Fredricks, Blumenfeld, & Paris, 2004), making it potentially malleable to pedagogical reforms.…”
mentioning
confidence: 95%
“…In addition, the School Engagement Scale/Questionnaire (SEQ) was developed as part of a large study in nine high schools that reported on ways that parents, peers, and communities infl uence students' commitment to, or engagement with, school (Steinberg et al, 1996 ) . This scale has subsequently been used by researchers trying to understand factors that explain differences in vocational attitudes and career development behaviors among subgroups of high school students (Perry, 2008 ;Wettersten et al, 2005 ) .…”
Section: Purposes and Usesmentioning
confidence: 99%
“…Kenny, Bluestein, Haase, Jackson, and Perry (2006) found that ethnic minority ninth-grade students' participation in career development programs contributed to increased feelings of school engagement. Perry (2008) also examined career development and school engagement among ninth-grade students of color and found that students' involvement in career planning activities had a considerable impact on self-report measures of behavioral and attitudinal aspects of school engagement.…”
Section: Career Development For Middle School Students Of Colormentioning
confidence: 99%